O papel da resiliência nas tarefas de escuta dicótica em adolescentes em situação de risco social - Lima, Mariana Batista (2013)
This research has been structured based on two articles: a systematic review of literature and an empirical article. The review included 46 articles from the past 10 years, in order to verify which dichotic listening tests were most applied on adolescent population and which was the most frequent purpose. Those were analysed based on four topics: age group, most commonly used tests, purpose of dichotic listening tests and the most frequent pathologies.It was found that 39.13% of studies used the Consonant-vowel Dichotic Test, often used to verify cerebral laterality.Digits Dichotic Test was present in 28.26% of the studies, followed by 15.21% of Alternate Dissyllable Test (SSW). The most frequent aim was to analyse auditory laterality (21.73%). As for the empirical study, it was attended by 40 adolescents aged between 9 and 15 years, all male. They were separated in two groups (Vulnerables and Resilients) based on their performance in the Resiliency Scale for Children and Adolescent, in order to verify their performance in tasks of Auditory Processing and subscales of resiliency. The results indicated a tendency toward better performance on the Resilient group subscales and, in Auditory Processing tasks, results were significant on Digits Dichotic Test for left ear (binaural integration skills) and right ear (binaural separation skills).Dichotic listening tasks are nowadays seen as a fast, efficient, easily applicable alternative for verifying the performance of individuals of all ages in tasks of hemispheric integration and brain lateralization. Recent studies have shown differences in auditory processing tests performance of socially vulnerable adolescents. Thus, it is extremely important to understand which impact adverse social situations may have on cognitive functioning and, thenceforth, determine the best tests to be applied when the objective is to investigate the inter-hemispheric communication, brain lateralization and behavioral pattern of the Central Auditory Processing.